INFORMATION AND COMMUNICATION TECHNOLOGY USE IN HIGHER EDUCATION: PERSPECTIVES FROM STUDENTS - Kofi Bentum Wilson; Isaac Tete-Mensah; Kofi Agyenim Boateng (European Scientific Journal, ESJ, 2014)
This study presents an analysis of University of Education, Winneba students’ use of Information and Communication Technology (ICT). The study describes the ability of students’ in using a wide range of ICT devices to support their personal learning. The study used a self-answering questionnaire and focus-group-discussions (FGD) to collect data from students. A total of thousand five hundred (N = 1500) students were selected using stratified sampling. The data from the questionnaires were analysed using SPSS software to identify and compare students’ ICT use and ability. The findings revealed that a good number of the students had access to ICT tools and devices, and were competent in using a wide range of ICT tools and devices both for the context of academic and non-academic use. It was evident in the data that most students used this technology on a frequent basis. Furthermore, the results suggested that students used technologies within the objectivist model of teaching and learning. From the findings, academic programs need to provide students with activities that require creative use of ICT devices and tools to enhance their skills in the use of computers as an instructional tool for supporting teaching and learning.